PEMBINGKAIAN RUANG VISUAL DALAM DESAIN VIDEO MUSIK ANIMASI SABDA ALAM SEBAGAI SENI MENYAMPAIKAN PESAN KAMPANYE - Winny Gunarti Widya Wardani; Syahid Syahid; Taufiq Akbar (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
Animated music video is an audio-visual media design that is presented in an illustrative narrative with song accompaniment. This spectacle has become a model for campaign media design that has appeal, like the animated music video “Sabda Alam” by students of SMK Raden Umar Said Kudus, which won appreciation at the 2021 Balinale International Film Festival. “Sabda Alam” tells the story of the lives of birds endemic typical of Indonesia which is increasingly rare. This media campaign indirectly supports the Ministry of Environment's program to socialize the importance of protecting the rich diversity of wild birds in Indonesia. This spectacle is interesting to study because it conveys a message by relying on the power of images in visual space. This research aims to show the relationship of visual elements in visual space as meaningful entities. The research method is descriptive qualitative with data collection techniques in the form of literature studies, observations, and interviews. While the data analysis technique uses image composition analysis into the rule of three imaginary grids, both vertically and horizontally. The results show that